The Combination of Upper Limb Exercise and Respiratory Muscle Stretch Gymnastics on Dyspnea Among COPD Patients - Ulfa Nur Rohmah; Muhammad Amin; Makhfudli Makhfudli (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2020)
Introduction: Dyspnea becomes important to treat Chronic Obstructive Pulmonary Disease (COPD) patients that had an impact on the limitations of daily activities. The purpose of this study was to determine the effects of Upper Limb Exercise and  Respiratory Muscle Stretch Gymnastics combination on dyspnea among COPD patients. Methods: The design of this study was a quasi-experiment. The population was patients who diagnose COPD by spirometry in Surabaya City and Bangil Regency. The total sample was 56 respondents divided into 28 in the intervention group, and 28 in the control group used consecutive sampling. The independent variables were the combination of Upper Limb Exercise and Respiratory Muscle Stretch Gymnastics. The dependent variable was dyspnea. Data were collected using the mMRC Dyspnea Scale. Interventions were given three times a week for a month.  Wilcoxon Sign Rank Test to analyzed before and after and Mann Whitney Test to determine between the intervention group and the control group. Results: The result showed that the intervention group was significant differences between dyspnea before and after the intervention with a value of 0.001 (p <0.05), but the control group was not with a value of 0.160 (p>0.05). There were differences in dyspnea values between the intervention group and the control group with a value of 0.004 (p <0.05). Conclusions: the combination of Upper Limb Exercise and Respiratory Muscle Stretch Gymnastics has been shown to reduces dyspnea with COPD patients so that patients can perform as complement pharmacological therapy.